Arabic Phonology (A Generative Analysis) - Nurjannah Nurjannah (Jurnal Scientia, 2024)
The aim of the research is to determine and analyze the form of transcription of Arabic phenotes, description and naming of Arabic language segments, description of Arabic language segments according to different characteristics and Arabic phonological processes. Data was taken using Arabic phonology with a review of generative analysis as a theoretical framework. Generative analysis is used to process the birth structure which can produce phonetic images. From the analysis results obtained it is concluded that 1) if the smoothed and loudened sounds meet then one of them is reversed. Example (if al) of the word (fa'ala). Apart from that, the sound of the letter j (waw) is sharpened, while the letter (ta') is softened j, 2) the transfer of air flow from the mouth to the nose or vice versa. The nature of sound is divided into two, namely the first exhalation of air through the mouth when speaking and is generally found in Arabic such as dal and la'. Both of them come out through the nose like the letters ? min and nun. The letters m ba turn into ? (mim) or the sound that passes from the mouth (ba') changes to the nasal sound (miim) as the combination of nin and lam in the example, 3) Shifting sound makhraj. There are various forms of assimilation from the original makhraj to other makhraj, many of which are found replacing the letter ^ with characteristics typical of modern Arabic dialects, such as when Egyptians pronounce (4->j±kU ) changed to (4j). and 4) Change in the nature of the sound from loud to soft. This assimilation is often found in idgham which consists of idgham mutamasilain, Idgham mutajanisasin, and Tdgham mutaqaribain